Efeitos da atividade física regular sobre parâmetros antropométricos e funcionais de mulheres jovens e idosas - Rogatto, Gustavo Puggina [UNESP]; Gobbi, Sebastião [UNESP] (My University, 2001)
The aim of the present study was to verify the strength levels and the arm cross-sectional-area (AMB) of young and old women who practice physical activity regularly. Thirty female subjects were selected and distributed into two groups: young (G1) and old (G2). They were evaluated on maximal voluntary strength of elbow flexor muscle by 1RM (one-maximal repetition) test (biceps curl), and the AMB, through the measures of arm circumference (CB) and triceps skinfold (DCTr), which were then used with the equation proposed by Frisancho (1984): AMB (cm2) = [(CB - pDCTr)2 / 4p] - 6.5, in both dominant (MD) and non dominant (MND) arms. Strength (kg) and AMB (cm2) were analyzed by ANOVA to a significance level of 5%. The G2 strength level was significantly (p<0,01) lower than G1, in both MD and MND. G2 showed a higher AMB only in the MND. Interpretation of these results led to the conclusion that, despite the aging process, regular practice of physical activity can prevent the loss of muscle mass. However, the capacity to generate force decreases with age, that is, for the same muscle mass the older people show lower levels of maximal voluntary contraction.
Effects of regular physical activity on anthropometric and functional parameters in young and old women
Keywords: Aging; Anthropometry; Exercise; Muscular strength